2020
DOI: 10.3390/ijerph17114046
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Needs Satisfaction and Frustration in Young Athletes: Factor Structure and Invariance Analysis

Abstract: Sports research has been focused on the assessment of basic needs satisfaction, considering its absence as a representation of needs frustration. However, recent findings have suggested needs satisfaction and frustration as asymmetrical factors leading to differentiated outcomes. An accurate measurement of needs poses itself as a crucial aspect, facilitating coaches’ understanding of athlete’s motivational processes. This study aimed to examine the psychometric proprieties of the Basic Psychological Needs Sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…According to SDT, autonomy, competence and relatedness are the three BPNs, which play a key role in motivation and well-being. Studies conducted with Portuguese athletes showed that autonomy satisfaction and frustration were the most reliable predictors of motivation [32,33], while in terms of coaching, autonomy-supportive behavior proved to be effective in satisfying young swimmers physiological needs [34]. As a result, it can be hypothesized that restricting autonomy in a bubble structure with strict COVID-19 related containment measures might negatively affect an athlete's motivation and consequently, the performance of the given athlete.…”
Section: Discussionmentioning
confidence: 99%
“…According to SDT, autonomy, competence and relatedness are the three BPNs, which play a key role in motivation and well-being. Studies conducted with Portuguese athletes showed that autonomy satisfaction and frustration were the most reliable predictors of motivation [32,33], while in terms of coaching, autonomy-supportive behavior proved to be effective in satisfying young swimmers physiological needs [34]. As a result, it can be hypothesized that restricting autonomy in a bubble structure with strict COVID-19 related containment measures might negatively affect an athlete's motivation and consequently, the performance of the given athlete.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recommendations mentioned have been considered by several authors in Portugal, when analysis of measurement model invariance as include in questionnaire validation in sport and exercise psychology (e.g., Cid et al, 2020b ; Monteiro et al, 2020 ; Rodrigues et al, 2021b ; Teixeira et al, 2021 ).…”
Section: Multigroup Analysismentioning
confidence: 99%
“…Among the indexes presented for acceptable measurement invariance, CFI was chosen as the main criterion because RMSEA and SRMR tend to over reject an invariant model when sample size is small, particularly when using SRMR for testing loading or residual variance invariance (Chen, 2008). Some of the recommendations mentioned have been considered by several authors in Portugal, when analysis of measurement model invariance as include in questionnaire validation in sport and exercise psychology (e.g., Cid et al, 2020b;Monteiro et al, 2020;Rodrigues et al, 2021b;Teixeira et al, 2021).…”
Section: Multigroup Analysismentioning
confidence: 99%
“…This measure would be very helpful for coaches and practitioners who wish to optimize performance and well-being. While sport psychology, specifically using the SDT model, may still be in its infancy in Portugal, recent studies (Monteiro et al., 2020; Rodrigues et al., 2020) have suggested that assessing and examining athletes’ motivation is crucial to facilitating a coach’s engagement and connectedness with an athlete’s well-being and self-determined motivation.…”
Section: Introductionmentioning
confidence: 99%